The Cycling Brain in the Workplace: Does Workload Modulate the Menstrual Cycle Effect on Cognition? - Xu, Min; Chen, Dandan; Li, Hai; Wang, Hongzhi; Yang, Li-Zhuang (Frontiers in Behavioral Neuroscience, 2022)
Recent decades have witnessed increased research efforts to clarify how the menstrual cycle influence females' cognitive and emotional functions. Despite noticeable progress, the research field faces the challenges of inconsistency and low generalizability of research findings. Females of re-productive ages are a heterogeneous population. Generalizing the results of female undergraduates to women in the workplace might be problematic. Furthermore, the critical cognitive processes for daily life and work deserve additional research efforts for improved ecological validity. Thus, the present study investigates cognitive performance across the menstrual cycle using a sample of young nurses with similar duties. We developed a mini-computerized cognitive battery to assess four mental skills critical for nursing work: cognitive flexibility, divided attention, response inhibition, and working memory. Participants completed the cognitive battery at menses, late-follicular, and mid-luteal phases. In addition, they were classified into low- and high workload groups according to their subjective workload ratings. Our results demonstrate a general mid-luteal cognitive advantage. Besides, the present study reveals preliminary evidence that workload modulates the menstrual cycle effect on cognition. Only females of low workload manifest the mid-luteal cognitive advantage on divided attention and response inhibition, implying that a suitable workload threshold might be necessary for regular neuro-steroid interactions. The present study thus advocates the significance of research focusing on the cycling brain under workloads.